Negotiating identities online: A quantitative exploration of Egyptian women's social media gratifications, challenges, and perceived portrayals - Selim, Nadeen; Khadragy, Saada; Hassan, Dalia; Hegazy, Asmaa; Ali, Sajjad (International Journal of Innovative Research and Scientific Studies, 2025)
The purpose of this study is to explore how influential Egyptian women (social media influencers and celebrities) express themselves and how they are perceived by the public. It also investigates the social roles and traits associated with the sample, Instagram post objectives, common topics discussed in Instagram posts, tone of voice delivered through post content and accompanying captions. The current study is a descriptive study that conducted a thorough visual content analysis of posts on Instagram taken and posted by five of the most influential women on Instagram as selected by Egyptian teenagers through a questionnaire. This study uses visual, quantitative content analysis to examine how influential Egyptian women are portrayed on Instagram. The researcher used a sample of 350 Instagram posts from five female Egyptian Instagram influencers, and celebrities. The study results demonstrate that influential Egyptian women on Instagram are primarily positive and evolving. The study results confirmed the existence of a statistically significant correlation between having a modern context of identity and showing sexualized body parts. In addition, there is a correlation of statistical significance between wearing a headscarf and having a "modest" context of identity. In addition, Instagram's representation of powerful Egyptian women indicates that they are primarily self-assured models who positively appeal to their audience about beauty and fashion. Most of their Instagram posts feature veiled women who seem to be self-sufficient. Almost all their Instagram posts are images accompanied by English-language captions.